Comparative Evaluation of Cytologic and Histologic Grading in Invasive Ductal Carcinoma Breast - Saloni Singhla; Varun Prasad; Srijan Srivastav (GAIMS Journal of Medical Sciences)
Background: Accurate pathological diagnosis is crucial for further treatment and estimation of an outcome in cases of breast cancer. The cytologic grade may provide information about the aggressive behavior of the tumor, thus guiding optimal therapy with prognostic information. The widely used Nottingham histologic grading method is a tumor grading system with strong prognostic connections.